Efficacy of Antimicrobial-Impregnated Catheters for Prevention of Bloodstream Infections in Pediatric Patients: A Meta-Analysis - Lai, Li; Yue, Xuan (Frontiers in Pediatrics, 2021)
Background: Multiple Randomized controlled trials (RCTs) have evaluated the efficacy of antimicrobial-impregnated catheters to prevent catheter-related blood stream infections (CRBSI). However, the RCTs showed contradictory results, the studies were limited in sample size and methodology quality. Thus, we conducted a meta-analysis to overcome these RCT limitations. Methods: We designed a meta-analysis of RCTs comparing antimicrobial-impregnated and conventional catheters for prevention of CRBSI. We conducted a detailed search of various databases for RCTs published before November 2019. We calculated mean differences (MDs) and pooled odd ratios (ORs) with 95% confidence intervals (CIs) using a random effects model. Results: We included 5 RCTs with a total of 2294 patients. The incidence of CRBSI between the two groups was 0.50 (95% CI, 0.19–1.27), with evidence of heterogeneity (I2=55%). The difference was not statistically significant (p=0.15). On sub-group analysis based on the age of the sample, there was no difference in the rate of CRBSI in neonatal population [0.42 (95% CI, 0.08–2.27 I2=61% p=0.31] as well as pediatric population [0.45 (95% CI, 0.12–1.67 I2=39% p=0.23]. The summary OR on the incidence of catheter colonization between antimicrobial-impregnated and conventional catheters was 0.64 (95% CI, 0.17– 2.35), with no evidence of heterogeneity (I2=0%) and a non-significant difference (p=0.50). Conclusions: To conclude, analysis of limited number of heterogenous studies mostly with small sample indicates that the CRBSI and catheter colonization rates are similar between conventional and antimicrobial-impregnated catheters in the paediatric and neonatal population. There is an urgent need of large-scale RCTs focussing on different antimicrobial-impregnated catheters in these patients to further enhance current evidence.